Generation Z perception of national online shopping day on Shopee e-commerce - Sentot Basuki Prayitno (Junal Ilmu Manajemen, 2023)
National Online Shopping Day or what is known as HARBOLNAS is a day when Shopee invites the public to recognize the convenience of online shopping. This is because Shopee provides many free shipping promotions with a minimum purchase so it changes people's perceptions of online shopping. However, from this phenomenon, people also think that this can lead to consumptive behavior because it can make people tempted by the attractive promos offered. Public perception of online shopping results in a lot of competition that exists between e-commerce causing each e-commerce to offer promotions to each other in attracting consumers to shop. This study aims to determine public perceptions of online shopping resulting in a lot of competition that exists between e-commerce causing each e-commerce to offer promotions to each other in attracting consumers to shop. This research method uses qualitative methods with a descriptive approach, with data collection methods using in-depth interviews and observations using Google Forms which are shared via Instagram and Whatsapp to find and filter information. There were 10 informants majoring in management at Sampoerna University. The data analysis technique uses the interactive model analysis of Miles, Huberman, and Saldana, namely through the stages of data collection, data condensation, data presentation, and drawing conclusions. The results of this study indicate that the majority of informants have positive perceptions of the many promos, discounts, free shipping, vouchers, cashback, easy payment systems, as well as complete and up-to-date goods. Based on these perceptions, it can be concluded that the appearance of Shopee and brand ambassadors did not influence the informants.